STRATEGI GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR SISWA KELAS VI DI SD NEGERI RANCAKALAPA II - Rahma Ilanuri Az zahra; Muhammad Soleh Hapudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning motivation of some sixth-grade students at SD Negeri Rancakalapa II, as reflected in their lack of participation and attention during the learning process. The study aimed to analyze teachers’ strategies in fostering the learning motivation of sixth-grade students at SD Negeri Rancakalapa II and to identify the supporting and inhibiting factors encountered in the learning process. The research employed a qualitative approach with a descriptive method. The research subjects consisted of one teacher and six sixth-grade students. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using the Miles and Huberman model with triangulation and member checking techniques to ensure data validity. The findings revealed that teachers’ strategies, such as the use of varied teaching methods, attractive learning media, praise and rewards, and personal approaches, were able to increase students’ participation, interest, and enthusiasm for learning. Supporting factors included the availability of facilities and infrastructure, support from the school environment, and good relationships between teachers and students. Meanwhile, inhibiting factors included differences in students’ characteristics, family backgrounds, and varying levels of learning readiness. This study concludes that the implementation of creative, adaptive, and student-centered learning strategies plays an important role in improving students’ learning motivation and the quality of learning in elementary schools. Keywords: Teacher Strategies, Learning Motivation, Sixth-Grade Students.